Óleos essenciais utilizados como conservantes em cosméticos - Gomes, Gabriela Freitas (Brasil, 2024)
Plants have several medicinal properties, in addition to producing essential oils rich in compounds with various activities, including aromatherapy, cooking, medicinal treatments and mainly antimicrobial properties, which can act on pathologies and in cosmetic formulations. Essential oil used as a natural preservative is considered an excellent alternative, due to its low risk of toxicity and cost, since synthetic preservatives, despite their proven efficiency, can present a risk of hypersensitivity to those who use the product, increasing the desire of the its reduction. This study aims to describe the use of essential oils as preservatives in cosmetics. This is a narrative-type bibliographical review. 45 articles were found with the proposed theme, of which 22 were excluded and nine species of plants were identified that contained essential oils with antimicrobial activity in cosmetic products, namely Calamintha officinalis, Cinnamomum verum, Cinnamomum zeylanicum, Crithmum maritimum, Lavandula angustifólia, Lippia origanoides, Melaleuca alternifolia, Rosmarinus officinalis and Thymus vulgaris, concluding that they are excellent candidates for natural preservatives, and could replace the use of traditionally used preservatives in the future. However, more in-depth studies are needed in relation to the species found, so that in the future they can operate in this field, contributing to the well-being of those who consume and the environment.